Validation of the Brazilian version of the Attentional Function Index Validación de la versión brasileña del Attentional Function Index Validação da versão brasileira do Attentional Function Index - Carla Klava dos Reis Dutra; Edinêis de Brito Guirardello (Universidade de São Paulo, 2013)
OBJECTIVES: To assess the reliability and validity of the Brazilian version of the Attentional Function Index. METHOD: Methodological study. The sample was made up of 138 students from an undergraduate nursing course. The psychometric properties were assessed through the convergent construct validity, using the Brazilian version of the Attentional Function Index and the Portuguese-language version of the Profile of Mood States instrument, while the reliability was measured by its internal consistency, expressed by the Cronbach Alpha Coefficient. RESULTS: The Cronbach Alpha Coefficient was 0.86 for the total score, and varied from 0.64 to 0.86 in the three subscales. A strong significant negative correlation (r=-0.64; p<0.0001) was obtained for the convergent validity. CONCLUSION: The Brazilian version of the Attentional Function Index resulted in satisfactory levels of validity and reliability, demonstrating its viability for use in practice and in undertaking further research. OBJETIVOS: Evaluar la confiabilidad y validez de la versión brasileña del Attentional Function Index. MÉTODO: Estudio metodológico. La muestra abarcó a 138 estudiantes del curso de pregrado en enfermería. La propiedades psicométricas fueron evaluadas mediante la validez de constructo convergente, con el uso de la versión brasileña del Attentional Function Index y la versión en portugués del Profile of Mood States, y la confiabilidad mediante la consistencia interna, expresa por el Coeficiente Alfa de Cronbach. RESULTADOS: El Coeficiente Alfa de Cronbach correspondió a 0,86 para el score total, y varió de 0,64 hasta 0,86 en las tres sub-escalas. Fue encontrada correlación significativa negativa de fuerte magnitud (r=-0,64; p<0,0001) para la validez convergente. CONCLUSIONES: La versión brasileña del Attentional Function Index resultó en niveles de validez y confiabilidad satisfactorios, demostrando la viabilidad de su utilización y la práctica y en el desarrollo de nuevas investigaciones. OBJETIVOS: avaliar a confiabilidade e validade da versão brasileira do Attentional Function Index. MÉTODO: estudo metodológico. A amostra foi composta por 138 estudantes do curso de graduação em enfermagem. As propriedades psicométricas foram avaliadas pela validade de construto convergente, com o uso da versão Brasileira do Attentional Function Index e a versão em português do instrumento Profile of Mood States e a confiabilidade por meio da consistência interna, expressa pelo coeficiente alfa de Cronbach. RESULTADOS: o coeficiente alfa de Cronbach foi de 0,86 para o escore total, e variou de 0,64 até 0,86, nas três subescalas. Obteve-se correlação significativa negativa de forte magnitude (r=-0,64; p<0,0001) para a validade convergente. CONCLUSÕES: a versão Brasileira do Attentional Function Index resultou em níveis de validade e confiabilidade satisfatórias, demonstrando a viabilidade da sua utilização na prática e desenvolvimento de novas pesquisas.